Didactic Design of Mathematics Learning to Improve Conceptual Understanding of Triangles and Quadrilaterals Based on Green Numeracy at a Private Islamic Junior High School - Samsuriadi Samsuriadi (Nashir Al-Kutub Indonesia, 2026)
Students still experience learning obstacles in understanding the concepts of triangles and quadrilaterals, particularly in distinguishing base and height, applying area formulas to non-routine problems, and connecting learning with real-life contexts, resulting in a gap between procedural and conceptual knowledge. This study aims to describe the learning obstacles experienced by students in understanding the concepts of triangles and quadrilaterals, and to design and test the effectiveness of a green numeracy-based didactic design in improving students’ conceptual understanding. This study employed a descriptive qualitative approach with a Didactical Design Research (DDR) design consisting of prospective, metapedadidactic, and retrospective analysis stages. Participants were 33 seventh-grade and 32 eighth-grade students at a private Islamic junior high school in East Lombok Regency, aged 12–14 years, selected through purposive sampling. Instruments included a semi-structured interview guide, an observation sheet, a five-item written test, and a document checklist. Data were analyzed using a qualitative descriptive approach with didactic analysis, involving data reduction, data display, linkage with the Theory of Didactical Situations, triangulation, and conclusion drawing. The results showed that students experienced ontogenic, epistemological, and didactical obstacles, reflected in a gap between memorized formulas and conceptual understanding; following the implementation of the green numeracy-based didactic design, significant improvements occurred in conceptual understanding, learning engagement, and student confidence; and learning that connected real-world measurement with the surrounding environment was shown to encourage students to construct understanding independently rather than merely repeating formulas. This study concludes that the green numeracy-based didactic design effectively addresses learning obstacles in triangles and quadrilaterals. Future researchers are recommended to expand the participant pool, extend the implementation duration, and integrate technology as well as more diverse environmental contexts.